مسار تنمية جانب العرض في الاقتصاد العراقي (المجلة العراقية للعلوم الاقتصادية, 2018)
This paper analysis the economic growth path in the Iraqi economy. This economy has realized a high economic growth rate over the last few years and an appropriate financial abundance. But noted that this situation does not mean that there is a tangible improvement in it's economic performance , because a substantial portion of economic growth is driven not by non – oil activity but by mining sector as a result of the growing contribution of oil exports. Increased oil export does not automatically breed economic growth, but it can help to stimulate the aggregate economic activity. The development of the domestic production of products and services is core driver of growth in developing countries. Manufacturing and the productive businesses require the circumstances to help increase economic growth. These circumstances include favorable exchange rate policy, excess to higher investment rate in both physical and social or human capital such as infra structure and education. Economic growth also comes from increase in the quality and quantity of human capital to improve the country's absorption capacity. More efficient exploitation of the rare productive resources can promote economic growth.